Digital maturity and its determinants in General Practice: A cross-sectional study in 20 countries - Teixeira, Fábia; Li, Edmond; Laranjo, Liliana; Collins, Claire; Irving, Greg; Fernandez, Maria Jose; Car, Josip; Ungan, Mehmet; Petek, Davorina; Hoffman, Robert; Majeed, Azeem; Nessler, Katarzyna; et al. (Frontiers in Public Health, 2023)
Background: The extension to which digital technologies are employed to promote the delivery of high-quality healthcare is known as Digital Maturity. Individuals’ and systems’ digital maturity are both necessary to ensure a successful, scalable and sustainable digital transformation in healthcare. Digital maturity in primary care has been scarcely evaluated. Objectives: This study assessed the digital maturity - as a whole and in its dimensions - in General Practice and evaluated how participants’ demographic characteristics, practice characteristics and features of Electronic Health Records (EHRs) use are associated with digital maturity. Methods: General Practitioners (GPs) across 20 countries completed an online questionnaire between June and September 2020. Demographic data, practice characteristics and features of EHRs use were collected. Digital maturity was evaluated through a framework built upon usage, resources and ability (divided in this study in its collective and individual components), interoperability, general evaluation methods and impact of digital technologies. Each dimension was rated as 1 or 0. The digital maturity score is the sum of the six dimensions and ranges from 0 to 6 (maximum digital maturity). Multivariable linear regression was used to model the total score, while multivariable logistic regression was used to model the probability of meeting each dimension of the score. Results: 1,600 GPs (61% female, 68% Europeans) participated. GPs had a median digital maturity of 4 (P25-P75: 3-5). Positive associations with digital maturity were found for: being male (B=0.18 [95%CI 0.01;0.36]), use of EHRs for longer periods (B=0.45 [95%CI 0.35;0.54]) and higher frequencies of access to EHRs (B=0.33 [95%CI 0.17;0.48]). Practising in a rural setting was negatively associated with digital maturity (B=-0.25 [95%CI -0.43;-0.08]). Usage (90%) was the most acknowledged dimension while interoperability (47%) and use of best practice general evaluation methods (28%) were the least. Shorter durations of EHRs use were negatively associated with all digital maturity dimensions (aOR from 0.09 to 0.77). Conclusions: Our study demonstrated notable factors that impact digital maturity and exposed discrepancies in digital transformation across healthcare settings. It provides a roadmap for policymakers to develop more efficacious interventions to hasten and take the best advantage of digital transformation in General Practice.